Animal models for the study of human disease - Conn, Patrick Michael 1949-2016 (Academic Press is an imprint of Elsevier, 2017)
Animal Models for the Study of Human Disease, Second Edition, provides needed information on model sharing, animal alternatives, animal ethics and access to databanks of models, bringing together common descriptions of models for busy researchers across biomedical and biological sciences. Offering easily searchable advantages and disadvantages for each animal model and organized by disease topics, this resource aids researchers in finding the best animal model for research in human disease. Organized by disease orientation for ease of searchabilityProvides information on locating resources, animal alternatives, and animal ethicsCovers a broad range of animal models used in research for human diseaseContributed by leading experts across the globeExpanded coverage of diabetes and neurological diseases